The Correlation of Students’ Motivation and Reading Comprehension of Tenth Grade IPS 1 at SMA N 3 Jambi City - Istiflah Istiflah; Yanti Ismiyati; Efa Silfia (Universitas Batanghari Jambi, 2022)
This research was conducted with the aim of analyzing the correlation of students’ motivation and reading comprehension, at tenth grade IPS 1 SMA N 3 Jambi City. This research was designed using quantitative research methods. The population of this study was the tenth grade students at SMA N 3 Jambi City, and the sample was IPS 1 students.This study uses questionnaire and test as research instruments. Then the results are assessed and. The questionnaire is adapted from previous research to collect motivation data. While the test is adapted from test Universitas Islam Negri Yogyakarta to collect the data of students’ reading comprehension. The highest score of students' motivation to reading was 72 points and the lowest score was 55 points and the average 62,7. The highest score test of a students’ score in reading was 85 and the lowest one was 25 and average 61. The data is calculated by using Pearson Product Moment to prove whether the hyphothesis of this research was significant or not, and the result of correlation analysis showed that the correlation coefficient ???????????? was -0,2538353. The value of ???????????? was consulted with Pearson’s product moment table (rtable) df 29 and significant level 5% and 1%. If ???????????? > rtable it meant that there was a positive correlation, and the hypothesis could be accepted. And if ???????????? < rtable it meant that there was not a positive correlation, and the hypothesis could be rejected.